About the Distinction between Working Memory and Short-Term Memory - Aben, Bart; Stapert, Sven; Blokland, Arjan (Frontiers in Psychology, 2012)
The theoretical concepts short-term memory (STM) and working memory (WM) have been used to refer to the maintenance and the maintenance plus manipulation of memory, respectively. Although they are conceptually different, the use of the terms STM and WM in literature is not always strict. Short-term memory and WM are different theoretical concepts that are assumed to reflect different cognitive functions. However, correlational studies have not been able to separate both constructs consistently and there is evidence for a large or even complete overlap. The emerging view from neurobiological studies is partly different, although there are conceptual problems troubling the interpretation of findings. In this regard, there is a crucial role for the tasks that are used to measure STM or WM (simple and complex span tasks, respectively) and for the cognitive load reflected by factors like attention and processing speed that may covary between and within these tasks. These conceptual issues are discussed based on several abstract models for the relation between STM and WM.